Developing Flood Vulnerable Map in Pasir Mas, Kelantan - Nur Aniza Mohmad Hanan (2020)
Kelantan is one of the state that received frequent flood disasters including Pasir Mas. The flood events are now intense because of localized physical and climatic factors, resulting in risks to the environment and population. Besides, by the difficult to identify the flood vulnerable area at Pasir Mas had become the main problem. The lack of comprehensive information which as a medium to communicating the flood risk, new unplanned developments and insufficient drainage systems made the situation more considerable. However, the development of a vulnerability map for flood risk of flooding management is still lacking. Vulnerability is the main construct in flood risk management. Therefore, this study aim identifies the variables which contribute to the risk of flooding based on the characteristics of the area and develop a flood vulnerability map using Geographical Information Systems (GIS) and Remote Sensing. In this study the land use data, the average amount of rainfall data and digital elevation model (DEM) data were used to produce a flood vulnerable map for the study area. The hydrology and weight overlay (spatial analyst) techniques were used to determine the flood vulnerable area on physical and climatic factors that cause flooding in Pasir Mas and to develop the flood vulnerable map in Pasir Mas. The vulnerability area had been determined based on the scale I (no vulnerability), 2 (low vulnerability), 3 (reasonable vulnerability), 4 (moderate vulnerability) and 5 (high vulnerability). The finding show that the area located at the water bodies recorded high vulnerable compared to other areas. Besides, from the flood vulnerable map, it can be observed that most of the area in Pasir Mas, Kelantan was falling under reasonable to high vulnerability classes. It is expected within this flood vulnerable map will able to assist the responsible parties to communicate and give an option to those affected people to ensure the effectiveness of the emergency response assistance and aid to victims for better preparedness capability.